2013
DOI: 10.1371/journal.pone.0053853
|View full text |Cite|
|
Sign up to set email alerts
|

Signaling Pathways of ESE-16, an Antimitotic and Anticarbonic Anhydrase Estradiol Analog, in Breast Cancer Cells

Abstract: The aim of this study was to characterize the in vitro action of 2-ethyl-3-O-sulphamoyl-estra-1,3,5(10)16-tetraene (ESE-16) on non-tumorigenic MCF-12A, tumorigenic MCF-7 and metastatic MDA-MB-231 breast cancer cells. ESE-16 is able to inhibit the activity of a carbonic anhydrase II and a mimic of carbonic anhydrase IX in the nanomolar range. Gene and protein expression studies using various techniques including gene and antibody microarrays and various flow cytometry assays yielded valuable information about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(59 citation statements)
references
References 64 publications
4
55
0
Order By: Relevance
“…Our preliminary data showed that the antiproliferative effect of ESE-16 is more potent on malignant cell lines than on non-tumorigenic cells [32]. The selectivity of ESE-16 towards metastatic breast cancer cells (MDA-MB-231) and breast adenocarcinoma MCF-7 cells was demonstrated in a comparison to its behavior toward non-tumorigenic MCF-12A cells [32].…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Our preliminary data showed that the antiproliferative effect of ESE-16 is more potent on malignant cell lines than on non-tumorigenic cells [32]. The selectivity of ESE-16 towards metastatic breast cancer cells (MDA-MB-231) and breast adenocarcinoma MCF-7 cells was demonstrated in a comparison to its behavior toward non-tumorigenic MCF-12A cells [32].…”
Section: Introductionmentioning
confidence: 79%
“…This was then followed with 24 h exposure under the same conditions. Appropriate controls were included: cells propagated in growth medium only; and a vehicle control composed of cells treated with DMSO with a final dilution never exceeding 0.02% (v/v) [32,33]. Actinomycin D (0.1 µg/ml in growth medium) was used as a positive control for the induction of apoptosis [33].…”
Section: General Cell Culture Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The altered mitochondrial membrane potential were detected by MitoCapture™ apoptosis detection kit produced by BioVision Inc. (Mountain View, CA, USA) as described previously [10]. Cells were cultured for 24 h and were exposed to compounds compounds (130 nM C9, 7.5 mM DCA and C9+DCA) for 24 h respectively.…”
Section: Methodsmentioning
confidence: 99%
“…C9 is another sulphamoylated analogue of 2ME and was in silico designed by our group [8,9,10]. C9 has improved bioavailability because of the ability of the sulphamoyl moiety to reversibly bind to carbonic anhydrase II present in erythrocytes and, in turn, this allows C9 to circumvent liver metabolism [11.]…”
Section: Introductionmentioning
confidence: 99%